2020
DOI: 10.3390/su12145505
|View full text |Cite
|
Sign up to set email alerts
|

Cinema as a Transmitter of Content: Perceptions of Future Spanish Teachers for Motivating Learning

Abstract: In recent decades, the diverse changes produced have accelerated the relationships regulated by media. Cinema was able to bring together moving image and sound for the first time, and as a result of its audiovisual nature, it is a particularly suitable resource for motivation in education. In this light, the teacher’s perception for its application in its initial formal stage is highly relevant. The main objective of our research, therefore, has been to analyze the perceptions of cinema as a didactic r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Aragón, on the other hand, is the Autonomous Community whose students watch the most fiction and animation films together (46.8%), Cataluña, where they watch the most fiction and documentary films together, and La Rioja and Cantabria, whose students most regularly watch fiction, documentary and animation films together. The data obtained are relevant due to the fact that, as they have stated [25], having a habit of consuming only fiction films determines a less positive perception of cinema as a didactic resource. On the other hand, the fact that students usually only watch documentaries on several types of films at the same time has a positive influence on their perception of the educational possibilities of cinema.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Aragón, on the other hand, is the Autonomous Community whose students watch the most fiction and animation films together (46.8%), Cataluña, where they watch the most fiction and documentary films together, and La Rioja and Cantabria, whose students most regularly watch fiction, documentary and animation films together. The data obtained are relevant due to the fact that, as they have stated [25], having a habit of consuming only fiction films determines a less positive perception of cinema as a didactic resource. On the other hand, the fact that students usually only watch documentaries on several types of films at the same time has a positive influence on their perception of the educational possibilities of cinema.…”
Section: Discussionmentioning
confidence: 91%
“…Ref. [25] found that a higher frequency of film viewing leads to a more positive perception of the potential of cinema as a didactic resource among teacher s degree students. These differences manifest themselves per student and per region and have their effect on the future application of cinema in the classroom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The above results conclude that it is possible to approximate the perception that future primary teachers have about documentary films. Broadly speaking, this allows documentary film to be profiled as a resource known by future teachers and perceived with some potential for use in this educational stage, as also noted by Lorenzo-Lledó, Lledó, Pérez-Vázquez, and Lorenzo (2020a). However, future primary teachers do not consume this type of audiovisual with a high frequency.…”
Section: Discussionmentioning
confidence: 97%
“…Avivi-Reich M. et al, through a controlled experiment, verified that the quiet learning environment for children's vocabulary memorization and learning has a positive effect [10]. Alejandro Lorenzo-Lledó et al were informed about the potential application possibilities of the film medium in pre-school and primary education in the form of a questionnaire and that film as a medium of education is expected and recognized by a wide range of students [11]. Based on teaching experiments, Santiago Pozo Sánchez et al demonstrated that the flipped classroom teaching model is more able to promote the motivation of primary and secondary school students than the traditional teaching model.…”
Section: Introductionmentioning
confidence: 99%